Distribution mapping of metal sediment using polarization data interpretation on the field “X” in PT Newmont Nusa Tenggara (PT NNT) - Sukri Arjuna; Adi Susilo; Sunaryo S (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
Geophysical research has been done on mapping distribution of metal deposits in the field "X" PT Newmont Nusa Tenggara using induced polarization geoelectric method pole-dipole configuration. Measurements performed using IRIS intrument type Elrec Pro where measurements of seven lines with length 2.3 km and electrode spacing 100 m. Induced polarization data furtheranalyzed by using Res2dinv version 3.56 and Surfer 10. Interpreted based on the parameters of chrageability and resistivity that correlated with regional geological information from the study area. As a result, the structure of rocks beneath the surface lithology research area consists of five units major rock that is tuffan claystone unit, sandstone tuffan unit, limestone unit, lava-brecciaunit, and andesite-basalt unit. Mineralization zone at the high chargeabilitas at 69.7 to 155 msec range supported by the low resistivity in the range of 4.21 to 26.5 Ωm which straight of anomalies in West-East direction at the depth of ± 50-400 m.